Non-communicable diseases and their associations with outpatient services utilisation: insight from a population-based survey in Malaysia - Jabrullah Ab Hamid; Awatef Amer Nordin; Suhana Jawahir; Adilius Manual; Iqbal Ab Rahim; Sarah Nurain Mohd Noh; Nur Elina Ab Mutalib; Nurul Salwana Abu Bakar (BMJ Open)
Objectives Multimorbidity has been recognised as a global public health issue, and individuals with multimorbidity have been found to have high healthcare utilisation. This study aims to estimate the prevalence of non-communicable diseases among adults in Malaysia, identify factors associated with multimorbidity, and assess the association between the number of non-communicable diseases and outpatient services utilisation.Design and setting A retrospective secondary data analysis using data from the National Health and Morbidity Survey 2019, a cross-sectional household survey among the population in Malaysia.Participants All adults aged 18 years and above.Outcome measures The two outcome variables were multimorbidity and outpatient services utilisation. Characteristics of respondents and those having multimorbidity were described using complex sample descriptive statistics. We used multivariable logistic regression to determine the associated factors of having multimorbidity and the association between the number of non-communicable diseases and outpatient services utilisation.Results Overall, 11 347 respondents were included in the analysis. This study found a prevalence of 11.4 (95% CI=10.43–12.39) for multimorbidity. Age, marital status and working status were the factors associated with multimorbidity. Adults with multimorbidity were high users of outpatient services (20.4%, 95% CI=17.5–23.7), approximately threefold of adults with no non-communicable diseases. In the final model, multimorbidity showed an adjusted OR of 3.28 (95% CI=2.48–4.32) for outpatient services utilisation.Conclusion Understanding factors associated with multimorbidity and the magnitude of the impact of having multimorbidity towards outpatient services utilisation could help in future planning for healthcare system transformation. The recently launched Health White Paper for Malaysia has emphasised primary healthcare as a critical component to achieve aspirations of the health system, which includes equity and responsiveness. Strengthening primary care services and improving patient navigation across healthcare levels are critical to supporting individuals with multimorbidity. Avenues for further research include exploring a wider range of conditions and assessing the longitudinal impact of multimorbidity on healthcare utilisation and health outcomes.